2008
DOI: 10.1261/rna.1208808
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed mitochondrial leucyl-tRNA synthetase suppresses the A3243G mutation in the mitochondrial tRNALeu(UUR) gene

Abstract: The A3243G mutation in the human mitochondrial tRNA Leu(UUR) gene causes a number of human diseases. This mutation reduces the level and fraction of aminoacylated tRNA Leu(UUR) and eliminates nucleotide modification at the wobble position of the anticodon. These deficiencies are associated with mitochondrial translation defects that result in decreased levels of mitochondrial translation products and respiratory chain enzyme activities. We have suppressed the respiratory chain defects in A3243G mutant cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 48 publications
2
33
2
Order By: Relevance
“…Indeed, the degree of increase in the rate of oxygen consumption in 43B-LARS2 cells correlated well with the increase in the rate of mitochondrial protein synthesis, suggesting that the improvement of mitochondrial translation was responsible for the increasing oxidative phosphorylation. However, this result was not in good agreement with the observation that the full recovery of respiration chain function occurred by means of overexpression of LARS2 in a mutant cybrid cell line carrying the A3243G mutation (39). This discrepancy may be attributed to different nuclear backgrounds, as in the case of cell lines carrying other mtDNA mutations (7,15).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Indeed, the degree of increase in the rate of oxygen consumption in 43B-LARS2 cells correlated well with the increase in the rate of mitochondrial protein synthesis, suggesting that the improvement of mitochondrial translation was responsible for the increasing oxidative phosphorylation. However, this result was not in good agreement with the observation that the full recovery of respiration chain function occurred by means of overexpression of LARS2 in a mutant cybrid cell line carrying the A3243G mutation (39). This discrepancy may be attributed to different nuclear backgrounds, as in the case of cell lines carrying other mtDNA mutations (7,15).…”
Section: Discussioncontrasting
confidence: 66%
“…In addition, the modified human FARS2 displayed significantly improved aminoacylation efficiency for the mitochondrial tRNA Phe G611A mutation (32). Alternatively, an increasing LARS2 expression in 43B cells may facilitate the correct folding and stabilization of the hypomodified tRNA Leu(UUR) (39). Moreover, an improvement of aminoacylation of tRNA Leu(UUR) by high levels of LARS2 appeared to lead to more efficient processing of the longer RNA precursors (22,24), evidenced by the fact that a reduction in the RNA19 was observed in the 43B-LARS2 cell line compared with the parental 43B cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, by transforming the mutants with multicopy plasmids overexpressing tRNA interactors (e.g., mt protein elongation factor EF-Tu or cognate aaRS) we were able to suppress the defective phenotypes determined by the mutations and partially restore the steady-state levels of mutated tRNAs (Feuermann et al 2003;De Luca et al 2006. More recently, analogous results have been obtained in patient cell lines and cybrids (Park et al 2008;Rorbach et al 2008;Sasarman et al 2008;Li and Guan 2010). Additionally, we have shown that ValRS and LeuRS have cross-suppressive activities on mt tRNA Leu and tRNA Val yeast mutants and that suppression of yeast defects can be obtained by overexpression of orthologous human factors (Montanari et al 2010).…”
Section: Introductionsupporting
confidence: 58%
“…Accordingly, modification of the mt-tRNA binding domain of human mitochondrial phenylalanyl-tRNA synthetase significantly improved the aminoacylation efficiency of mttRNA Phe carrying the m611G>A MERRF mutation [70]. Overexpression of human mitochondrial valyl-or leucyl-tRNA synthetases increased, respectively, the steady-state levels of mutant mt-tRNA Val [71] or mt-tRNA Leu(UUR) [72], consistent with increased stability of the charged mt-tRNA. Also, overexpression of mitochondrial leucyl-tRNA synthetase rescued mitochondrial translation and respiration in cells carrying the A3243G MELAS mutation in mt-tRNA Leu(UUR) [73].…”
Section: Gene Therapy To Reduce or Compensate For Mutant Mtdnamentioning
confidence: 84%